Content validity of an analytical rubric of the design of didactic sequences as an improvement of the pedagogical practice of the teaching team from the socioformation approach - Guevara-Rodríguez, Guillermina (2021)
The educational context traditionally determines an administrative practice of planning and evaluation processes, in this sense, there is a lack of instruments to evaluate the design of didactic sequences with the challenge of granting knowledge that confront contextual problems; and make a teaching intervention with methodological bases for solving problems. The purpose of this study is to describe the design of a didactic sequence rubric for the improvement of pedagogical practice. The methodology was carried out through an instrumental study of content validity based on the socioformative approach with the following steps: 1) analysis of instruments at ends; 2) construction of a rubric with the focus of socioformation, 3) revision and improvement of the instrument by experts; 4) application of the instrument to a pilot group; and 5) validation of content by a group of judges in the educational area. The results with respect to the V of Aiken with a significance of p <0.05, show a value above 8.0. Some items whose level of significance was 0.71 were eliminated. The reliability analysis shows a value of Cronbach's alpha of 0.891, the Aiken and Cronbach coefficient methodologies applied, determined the content validity of the rubric. In conclusion, a pertinent instrument to evaluate the design of didactic sequences is presented, and the need to extend this study with an exploratory factor analysis that determines its construct validity is presented.